Dosimetry modeling of focused kV x‐ray radiotherapy for wet age‐related macular degeneration. Issue 10 (12th August 2020) - Yan, Huagang; Sun, Weiyuan; Mruthyunjaya, Prithvi; Beadle, Beth; Yu, Weihong; Kanwal, Bushra; MacDonald, Carolyn A.; Liu, Wu
Abstract : Purpose: Wet (neovascular) age‐related macular degeneration (AMD) is the leading cause of blindness in the United States. The mainstay treatment requires monthly intravitreal injection of anti‐vascular endothelial growth factor (anti‐VEGF) drugs, associated with multiple visits, high cost, and the risk of procedural injury and infection. Anti‐VEGF drugs inhibit the formation of neovasculature but do not directly attack it. Radiotherapy can destroy neovasculature and potentially also inhibit wet‐AMD associated inflammation and fibrosis not addressed by VEGF inhibitors. However, the current collimation‐based radiotherapy device uses fixed 4 mm beams, which are prone to overtreat or undertreat the choroidal neovascularization (CNV) lesions because of their various sizes and shapes. This simulation study evaluates personalized conformal treatment with focused kV radiation using cutting‐edge polycapillary x‐ray optics. Methods: Simulation of the polycapillary optics was achieved via Monte Carlo (MC)‐based three‐dimensional (3D) geometric ray tracing. Phase‐space files modeling the focused photons were generated. The method was previously verified by phantom measurements. The ultrasmall 0.2 mm beam focal spot perpendicular to the beam direction enables spatially fractionated grid therapy, which has been shown to preferentially damage abnormal neovascular blood vessels vs normal ones. Geant4‐based MC simulations of scanning while rotating beam delivery were performed to conformally treat three clinical cases of large, medium, and small CNV lesions with regular and grid deliveries. Dose delivery uncertainties due to positioning errors were analyzed, including ±0.75 mm displacement in the three orthogonal directions and ±5° vertical/horizontal rotation of the eyeball. Results: The simulated CNV treatments by 60‐kVp focused x‐ray beams show highly conformal delivery of dose to the lesion plus margin (0.75 mm) with sharp dose fall‐offs and controllable spatial modulation patterns. The 90%–10% isodose penumbra is <0.5 mm. With a prescription dose of 16 Gy to the lesions, the critical structure doses are well below the tolerance. The average CNV dose varies within 10% (mostly within 4%) due to 0.75‐mm linear displacements and 5‐degree gaze angle rotation of the eyeball. Conclusion: Focused kV technique allows personalized treatment of CNV lesions and reduces unwanted radiation to adjacent healthy tissue. The simulated dose distribution is superior to currently available techniques.